Organizational Learning through Unlocking Multiple Organizational Narratives: The Case of Telcotech - Jonczyk Sédès, Claudia (My University, 2005)
Countless publications on the future of management education and on qualifications needed at the workplace emphasize the need for learning from experience, (Smith, 2000). While practice can be viewed as a rich source of new knowledge and learning about management (Kim, 1999), the learners’ active participation in learning is essential to capture the learnings occurring in job assignments (Ulrich/Greenfield, 1995).
, 2005